An exploratory qualitative investigation of psychosocial determinants of parental decisions to support sport participation for youth with a mobility impairment. (October 2015) - Shirazipour, Celina H.; Latimer-Cheung, Amy E.; Arbour-Nicitopoulos, Kelly P.
Highlights: Parents play a key role in supporting sport for youth with a mobility impairment. Similarities and differences emerged between parents of athletes and non-athletes. The Health Action Process Approach aids in understanding parental support for sport. Abstract: Introduction: Parents of youth with a mobility impairment (MI) have an important influence on their children's sport participation. The current study consists of an exploratory qualitative investigation of the relevance of HAPA for understanding parental support behaviours for youth with MI's sport participation. Methods: Parents of youth athletes ( M age = 11.10; SD = 2.77) and non-athletes ( M age = 11.50; SD = 3.84) participated in semi-structured interviews with question development guided by the Health Action Process Approach (HAPA). Results: Constructs from HAPA were expressed as relevant to parental decisions, with differing subthemes emerging based upon parental group (i.e. parents of non-athletes or parents of athletes). Other constructs that emerged included barriers, facilitators, and resources. Discussion: Constructs from the motivational phase of HAPA were relevant for parents of athletes and non-athletes, while the volitional phase demonstrated utility for understanding the views of parents of athletes. Differences between the patterns of responses of both groups were apparent in how the constructs were expressed. Findings identify key areas for research, as well as practical applications. For example, future programs can target parental positions on specific HAPA constructs (e.g. risk perceptions) where differences were found between both groups of parents in order to promote parental decisions that support their children's sport participation.